(untitled) (Web of Teachers: Inderscience Research, 2026)
This article analyzes the issues of determining the effectiveness of teaching physics in general secondary schools based on the PISA (Programme for International Student Assessment) approach. The study examines methodological approaches aimed at developing students’ abilities to apply theoretical knowledge in practical situations, forming problem-solving competencies, and increasing functional literacy levels. Furthermore, a comparative analysis is conducted between traditional teaching methods and interactive, competency-based approaches rooted in PISA requirements. The research findings highlight the critical importance of tasks based on real-life contexts, analytical thinking, and experimental activities in physics education. The article substantiates that the effectiveness of education can be enhanced by utilizing modern assessment criteria and implementing innovative pedagogical technologies into the teaching process. Consequently, it is determined that lessons organized through the PISA approach significantly increase students’ independent thinking, problem-solving skills, and overall interest in the sciences.